Q-tip ear injury with stapes luxation into the vestibule-a case report - Lame, Cheikh Ahmedou; Ndiaye, Cheikhna Ba; Loum, Birame; Fall, Amat; Goumba, Alice; Diallo, Thierno Boubacar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Stapediovestibular luxation by Q-tip ear injury is a rare occurrence. The traumatic context associated with cochleovestibular symptoms should lead to a high index of suspiscion. Temporal bone CT scan confirms the diagnosis. The authors report a case of stapediovestibular luxation and discuss the management of this condition. An 8-year-old boy presented to our department for otalgia, hearing loss, and dizziness. The history revealed a penetrating right ear injury by Q-tip, which had occurred 5 days previously. ENT examination found a right peripheral vestibular syndrome with ipsilateral tympanic perforation. Tonal audiometry noted right cophosis. Temporal bone CT scan showed right side internal stapediovestibular dislocation. Middle ear inspection with oval window fistula repair and tympanic closure were performed. Postoperative outcomes showed complete resolution of vestibular symptoms without improvement of sensorineural hearing loss thresholds. Traumatic stapediovestibular dislocation by Q-tip ear injury is unusual. Early diagnosis, with precise lesion assessment and appropriate management resolve vestibular symptoms, prevent infectious complications. But, hearing outcomes are variable.